Problematizing philanthropy: how a historical study of the General Education Board in the US west puts the "social" in race and region as social constructs. Issue 2 (4th March 2017) - Janak, Edward; Helmsing, Mark
Abstract: This article explores how an examination of the philanthropic funding from the General Education Board (GEB) provided to the public schools in the western region of the US, particularly that impacting schools serving the historically marginalized cultures of the Latina/o, indigenous, and African American peoples, demonstrates just how fluid are the constructs of race and regionality. The article explores whether philanthropic funding followed the same racist and pecuniary patterns in the west/southwest as in the southeast and how actively researching that question reinforced the intersectionalities of race and region in defining the west as a social construct not conforming to geographic boundaries. Examining GEB funding should impact current thought regarding blindly accepting philanthropic influence in the public schools of the US.